Exploring the effect of relative advantage and challenge on customer engagement behavior with mobile commerce applications. - Japutra, Arnold; Molinillo-Jiménez, Sebastián; Utami, Ami Fitri; Ekaputra, Irwan Adi (My University, 2022)
This research explores the drivers of customer engagement behavior with mobile commerce applications (m-commerce apps), using the stimulus (S), organism (O), and response (R) framework. Customer engagement is conceptualized through four dimensions: co-developing, influencing, augmenting, and mobilizing behavior. The proposed model was tested using data collected from 717 users of m-commerce apps through an online survey. This study shows that relative advantage and perceived challenge positively influence customer perceptions of enjoyment and control, which leads to higher customer engagement behavior. Customers’ perceived enjoyment was also found to mediate the relationship between perceived relative advantage, perceived challenge, and three customer engagement dimensions (i.e., co-developing, influencing, and mobilizing behavior). By studying the factors that might be able to develop customers’ engagement behavior in m-commerce app settings, this research is a novel contribution to the literature, as previous studies in mobile apps focused more on adoption than user engagement behavior.
Keywords: Cosumidores - Hábitos y conducta; Internet - Compra; Customer engagement behavior; Relative advantage; Challenge; Control; Enjoyment; Mobile commerce application